Pengaruh Budaya Organisasi, Gaya Kepemimpinan dan Kepuasan Kerja terhadap Kinerja Pegawai Melalui Motivasi Pegawai sebagai Variabel Intervening pada Dinas Ketahanan Pangan, Kelautan dan Pertanian Provinsi DKI Jakarta Tahun 2020 - Edi Sugiyono; Rita Rahajeng S (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study uses primary data with a total of 130 respondents. The analysis used is multiple linear regression analysis (PLS) using SEM. The results showed that organizational culture had a negative and insignificant effect on employee motivation, leadership style and job satisfaction had a positive and significant effect on employee motivation. Organizational Culture, Leadership Style and Job Satisfaction have a negative and insignificant effect on employee performance. Organizational culture has no significant effect on employee performance through employee motivation, leadership style and job satisfaction have a significant effect on employee performance through employee motivation. Employee motivation has a positive and significant effect on employee performance.